2019
DOI: 10.5312/wjo.v10.i6.247
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral sequential femoral neck stress fractures in young adult with HIV infection on antiretroviral therapy: A case report

Abstract: BACKGROUND Femoral neck stress fractures are rarely encountered among young adults and are often associated with either repetitive excessive loading or underlying bone pathology. Preliminary research has indicated human immunodeficiency virus (HIV)/antiretroviral therapy (ART) as predisposing agents to osteopenia and osteoporosis related complications. We report a case of HIV/ART induced insufficiency fracture in a resource limited setting in Central India. Our aim is to increase awareness and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, the literature reports related to femoral neck stress fractures are mostly case reports on soldiers and athletes, and there are few reports on femoral neck stress fractures in elderly patients. [ 5 7 ] However, we found that these patients are the most accessible in the clinical setting. Therefore, it is crucial to diagnose these patients promptly and to intervene early and correctly.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…To the best of our knowledge, the literature reports related to femoral neck stress fractures are mostly case reports on soldiers and athletes, and there are few reports on femoral neck stress fractures in elderly patients. [ 5 7 ] However, we found that these patients are the most accessible in the clinical setting. Therefore, it is crucial to diagnose these patients promptly and to intervene early and correctly.…”
Section: Discussionmentioning
confidence: 94%
“…One type is a normal or abnormal stress repeatedly acting on a normal quality femoral neck, which can also be called a fatigue fracture and is usually seen in athletes and soldiers. [3,5,[28][29][30][31][32] Fatigue fractures may also be secondary to patients with abnormal femoral neck anatomy. [11,[33][34][35] The other type of fracture is an insufficiency fracture, in which the quality of the bone is reduced for various reasons, such as senile osteoporosis, postmenopausal osteoporosis, renal bone disease, vitamin D deficiency and other metabolic bone diseases, cortisol use, neurological sexual anorexia, and the use of certain drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On review of literature, very few case reports describing bilateral sequential neck fractures of femoral neck have been reported. Chaganty et al 8 reported a bilateral sequential femoral neck fracture in a 35-year-old HIV patient on ART.…”
Section: Discussionmentioning
confidence: 99%
“…Association with seizure disorders and electric shock injuries has also been reported[10-11]. Finally, this fracture pattern has been seen with long-term use of bisphosphonates, narcotic drug abuse, anti-retroviral therapy, and psychosomatic disorders, like anorexia nervosa[12-15].…”
Section: Introductionmentioning
confidence: 99%